The Cambridge companion to the epic - Bates, Catherine (New York : Cambridge University Press, 2010)
"Every great civilisation from the Bronze Age to the present day has produced epic poems. Epic poetry has always had a profound influence on other literary genres, including its own parody in the form of mock-epic. This Companion surveys over four thousand years of epic poetry from the Babylonian Epic of Gilgamesh to Derek Walcott's postcolonial Omeros. The list of epic poets analysed here includes some of the greatest writers in literary history in Europe and beyond: Homer, Virgil, Dante, Camões, Spenser, Milton, Wordsworth, Keats and Pound, among others. Each essay, by an expert in the field, pays close attention to the way these writers have intimately influenced one another to form a distinctive and cross-cultural literary tradition. Unique in its coverage of the vast scope of that tradition, this book is an essential companion for students of literature of all kinds and in all ages"--Provided by publisher.
14. Epic in translation / Paul Merchant
Bibliografija. - Kazalo
Access is available to the Yale community.
Keywords: Epic poetry -- History and criticism; epska književnost; epika